Linfócitos T CD8+ na Covid-19: avaliação de biomarcadores em formas clínicas leve e grave da doença - Aureliano, Francisco Sandro (2022)
Coronavirus Disease 2019 (COVID-19) is a highly transmissible acute respiratory disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The HCoVs of greatest epidemiological importance are MERS-CoV causing Middle East respiratory syndrome, SARS-CoV causing severe acute respiratory syndrome, and more recently SARS-CoV-2 causing COVID-19. SARS-CoV-2 is an RNA beta coronavirus and initially emerged in China in December 2019, where the first cases were associated with the Wuhan Seafood Wholesale Market, China. Since its emergence, cases of COVID-19 have spread across several countries, thus classifying it as a pandemic. Those infected with SARS-CoV-2 may have no symptoms or have symptoms ranging from mild to lethal. The current pandemic situation declared by the World Health Organization (WHO) in March 2020, due to the spread of SARS-CoV-2, has been challenging for health authorities to find both therapeutic and preventive solutions for the disease, as well as understand its effects on the human organism from an immunological point of view. Some described mainly report leukocyte alterations, with lymphopenia and a decrease in T cells, including CD8+ T cells. Changes in the subpopulation of CD8+ T lymphocytes have increased the production of expression levels of activation, proliferation, and modulation markers indicating that there may be specific CD8+ T cell responses in patients with COVID-19. Thus, the present study aimed to investigate the immunomodulatory mechanisms mediated by CD8 + T cells, correlating the clinical characteristics of patients recovered from mild and severe forms of COVID-19, in order to characterize the presence of prognostic markers. To this end, peripheral blood samples were obtained from recruited volunteers and distributed into control (CTL - n = 9), mild IgG - (n = 5), mild IgG+ (n = 6) and severe (n = 7) groups. Samples of PBMCs were obtained and incubated under 4 different conditions: unstimulated (medium), stimulated with SARS-CoV-2 peptides (Pool Spike CoV-2 and Pool CoV-2) and stimulated with Staphylococcal enterotoxin B (SEB). CD8+ T cells were analyzed and classified regarding the expression of markers of activation (CD38 and CD69), proliferation (Ki-67), as well as the production of the cytokine INF-ɣ and cytotoxic profile through the co-expression of granzyme B and perforin, and the degranulation marker CD107a between the control and recovered groups. Our analyzes generally demonstrate that both individuals who have mild COVID and are IgG+, and individuals who have severe clinical COVID-19 had a lower frequency of CD8+ T cells. In addition, the data also showed that the IgG- and/or IgG+ light groups showed an expressive production of activation markers CD69 and CD38, IFN – γ, and more cytotoxic CD8+ T cells. We can conclude that markers of activation, degranulation, and the pro-inflammatory cytokine IFN - γ may be possible prognostic markers for COVID-19 in the mild clinical form. This approach could guide investment in research in the area of Biotechnology, with an approach in the development of possible target therapies for these markers, or even the development of faster and more effective diagnostic tests in the prediction of serious diseases.